Nonpharmacological enhancement of cognitive function in Parkinson's disease: A systematic review. Issue 8 (20th February 2013) - Hindle, John V.; Petrelli, Annette; Clare, Linda; Kalbe, Elke
ABSTRACT Cognitive decline and dementia are frequent in patients with Parkinson's disease (PD). The evidence for nonpharmacological therapies in Alzheimer's disease and other dementias has been studied systematically, but the evidence is unclear for their efficacy in cognition and dementia in PD. An international collaboration produced a comprehensive, systematic review of the effectiveness and of nonpharmacological and noninvasive therapies in cognitively intact, cognitively impaired, and PD dementia groups. The interventions included cognitive rehabilitation, physical rehabilitation, exercise, and brain stimulation techniques but excluded invasive treatments, such as surgery and deep brain stimulation. The potential biases and evidence levels for controlled trials (CTs) were analyzed based on Cochrane and National Institute for Health and Clinical Excellence criteria. After exclusions, 18 studies were reviewed, including 5 studies of cognitive training, 4 of exercise and physical therapies, 4 of combined cognitive and physical interventions, and 5 of brain stimulation techniques. The methodology, study populations, interventions, outcomes, control groups, analyses, results, limitations, biases, and evidence levels of all reviewed studies were described. There were 9 CTs, including 6 randomized CTs (RCTs). Although 5 trials showed positive results, only 1 study of cognitive training achieved evidence grading of 1+ with a low risk of bias. There were no studies on PD dementia. Current research on nonpharmacological therapies for cognitive dysfunction and dementia in PD is very limited in quantity and quality. There is an urgent need for rigorous RCTs of nonpharmacological treatments for cognitive impairment and dementia in PD. © 2013 Movement Disorder Society